The application of artificial airway care for postoperative weaning patients with cerebral hemorrhage by failure mode and effect analysis mode - Tang, Xifei; Yue, Jianhe; Chen, Yao; Zhou, Runmei; Wang, Chanjuan; Zhang, Ting; Gan, Xiuni (Frontiers in Medicine, 2025)
ObjectiveTo investigate the application of artificial airway care under the Failure Mode and Effect Analysis (FMEA) mode in postoperative weaning patients with intracerebral hemorrhage (ICH).MethodsA total of 137 patients who met the inclusion and exclusion criteria were selected from an affiliated hospital of Chongqing Medical University. Using a random number table, 67 patients and 70 patients were randomly assigned to the control group and the experimental group, respectively. The control group received conventional care, while the experimental group received artificial airway care based on the FMEA mode for postoperative weaning patients with cerebral hemorrhage. Data was analyzed using SPSS 27.0 to compare the incidence of pulmonary infection, re-intubation, aspiration, sputum viscosity, and tracheal tube duration between the two groups.ResultsThe incidence of pulmonary infection, re-intubation, and aspiration in the experimental group was significantly lower than that of the control group (p < 0.05). After intervention, the state of sputum viscosity in the experimental group was significantly improved compared to the control group (p < 0.05). The PaO2 level in the arterial blood gas analysis was significantly higher in the experimental group after intervention (p < 0.05). Additionally, the tracheal extubation time in the experimental group was significantly shorter than that of the control group (p < 0.05).ConclusionArtificial airway care under the FMEA mode can effectively reduce the complications in postoperative weaning patients with cerebral hemorrhage, such as pulmonary infections, re-intubation, and aspiration. It can improve PaO2 levels and sputum viscosity in arterial blood gas analysis while reduce the tracheal tube duration, and ultimately promote patient recovery.